An anonymous girl [compact disc, unabridged] : - Hendricks, Greer; Pekkanen, Sarah (Macmillan Audio, 2018)
Participating in a psychological study under the mysterious Dr. Shields, Jessica endures intense, invasive sessions and oppressive behavioral restrictions before she begins to lose her grasp on reality.